(untitled) (GESTIÓN Y TENDENCIAS, 2021)
The environmental crisis facing our planet is driving the emergence of new patterns of production and exploitation, alongside the growth of customers with socially responsible purchasing behavior. If companies are to confront this new competitive reality and reach sustainable market segments, they must modify their current business models and develop new ones; doing so, however, carries the enormous difficulty of balancing people, development, and profit. This paper presents elements that help overcome this difficulty and facilitate the development of sustainable business models, and explains their importance.